Penggunaan Modul Digital Berbasis Game Based Learning Dalam Meningkatkan Keaktifan Siswa Pada Mata Pelajaran Al-Qur’an Hadist - Maliana Julia Saputri; Jasiah Jasiah (JOURNAL SAINS STUDENT RESEARCH, 2025)
in today's digital era, various kinds of digital platforms or education-based website pages are easily accessible so that they can be used to improve the quality of learning to be more varied and interactive. In addition, digital platform can also be used in developing digital teaching materials, one of which is the digital module teaching materials. The purpose of this article is to see if the use of Game-Based Learning-based Digital Module can increase students' activity in the subject of Al-Qur'an Hadist in the learning process at MTs Terpadu Berkah Palangkaraya. The method used in this study is Research and Development (R&D) with a 4D model. The results of this study show that there is an increase in student activity in the use of Game-Based Learning-based Digital Module as 95,8%.